Silicon slag increases melon growth and resistance to bacterial fruit blotch - Preston, Hailson Alves Ferreira; Nascimento, Clistenes Williams Araújo do; Preston, Welka; Nunes, Glauber Henrique de Souza; Loureiro, Francisco Leandro Costa; Mariano, Rosa de Lima Ramos (Acta Scientiarum. Agronomy, 2020)
Melon bacterial fruit blotch (BFB) is the major bacterial melon disease in Northeastern Brazil. We evaluated the effects of applying a silicon (Si) slag on BFB suppressiveness in two melons cultivars as well as in soil chemical attributes and plant growth and nutrition. Slag was incorporated into the soil at concentrations equivalent to 0.00, 0.12, 0.24, 0.47, 0.71, and 1.41 g kg-1 of silicon. Plants were inoculated with Acidovorax citrulli 20 days after emergence. Results showed that amending the soil with Si slag improved the resistance of two melon cultivars against bacterial fruit blotch. Such an effect is probably related not only to the Si uptake by plants but also to changes in soil characteristics and improvement in plant nutrition. Both hybrid cultivars (AF4945 and Medellín) increased biomass, nutrient and Si accumulation as a function of Si doses applied to soil. According to Si concentration and Si to Ca ratio in plant tissue, both cultivars are regarded as intermediary Si-accumulators. We also observed that an intermediate dose of Si (0.71 g kg-1) posed better results on controlling melon bacterial fruit blotch than the highest dose tested